Pengembangan Media Komik Digital Belajar Sejarah Untung Suropati (Besti) Berbasis Line Webtoon untuk Menunjang Kemampuan Berfikir Kronologis Peserta Didik - Khoiroh, Muhimatul; Widiadi, Aditya Nugroho (Universitas Hamzanwadi, 2025)
The research conducted originated from the problem of students who did not understand the historical value of the struggle of National Hero Untung Suropati chronologically. As many as 87.5% of students want learning media that can convey historical material using stories and pictures. The purpose of this research and development is to produce and test the effectiveness of digital comic media Learning History of Untung Suropati (Besti) on the ability to think chronologically of students in class XI-8 SMAN 2 Pasuruan. The research method used is the Research and Development method with a development model developed by Sugiyono which has 10 stages. The results showed that the validity of the product obtained from material experts was 81.73%, validation from media experts was 91.5%, and assessment from history teachers was 90.76%. The results of the product feasibility test in the small group trial conducted on 6 students obtained a percentage value of 81.3%, while the results of the large group trial conducted on 26 students obtained a percentage value of 81%. Research on effectiveness was also carried out by conducting pretests and posttests which showed differences before and after using the developed media. Based on this, the digital comic media Belajar Sejarah Untung Suropati (Besti) that has been developed can be classified as valid, effective, and suitable for use in learning history.